Causes and implications of Mid- to Late Holocene relative sea-level change in the Gulf of Kachchh, western India. (March 2021) - Sharma, Shubhra; Chauhan, Gaurav; Shukla, Anil Dutt; Nambiar, Romi; Bhushan, Ravi; Desai, Bhawanisingh G.; Pandey, Shilpa; Dabhi, Madhavi; Bhandari, Subhash; Bhosale, Suraj; Lakhote, Abhishek; Juyal, Navin
Abstract: The relict intertidal deposits from the Kharod River Estuary, Gulf of Kachchh, and the distal end of Kori Creek are used to infer the Mid- to Late Holocene relative sea-level (RSL) change in western India. Employing sedimentology, geochemistry, palynology, ichnology, and optical and radiocarbon dating, the study suggests the dominance of fluvial activity between 16.5 ± 1.6 and 9.9 ± 0.7 ka. After 7 ka (7.3 ± 0.4, 6.8 ± 0.5 ka), the sea level showed a positive tendency until 4.7 ± 0.2 ka. The tectonically corrected Mid-Holocene RSL change is estimated as 1.45 ± 0.33 m between 7 and 5 ka. The study suggests that the Mid-Holocene RSL high was due to the meltwater contribution from the Himalayan cryosphere, with subordinate contribution from glacio-isostatic adjustment and crustal subsidence. The Late Holocene tectonically corrected RSL change at 1 ka (1.1 ± 0.1 ka and 1045 ± 175 cal yr BP) is estimated as 0.53 ± 0.43 m. This is ascribed to monsoon wind-driven tidal ingression that might have affected the tidal amplitude positively. The study suggests that the Mid-Holocene RSL change did not play a deterministic role in the abandonment of the Harappan coastal settlements.